THE IMAGINARY THAT DENOUNCES: AMAZONIAN LEGENDS, DIALOGUE, AND CRITICAL THINKING THROUGH A DIDACTIC SEQUENCE IN THE 9TH GRADE OF A PUBLIC SCHOOL IN PARINTINS - Edinelza Macedo Ribeiro; Elton Gonçalves dos Santos (Revista Gênero e Interdisciplinaridade, 2026)
From the perspective of understanding that a territory can possess enormous potential in cultural products, without these acquiring a form of cultural resources suitable for promotion by tourism promoters and use by visitors with cultural interests, the importance of valuing existing resources is highlighted. In this context, fishing tourism has been one of the tourism segments gaining strength. This article aims to show the potential of the São José do Paraná do Espírito Santo de Cima community as a way to promote fishing tourism and the conservation of natural and cultural heritage. This community is located in the rural area of ​​the municipality of Parintins and falls within the Nhamundá Environmental Protection Area. This is an environmental conservation unit that aims to protect natural and cultural heritage. The community has two types of ecosystems, one of terra firme and the other of floodplain area. The research is characterized as qualitative in nature. According to Minayo (2001), this type of research works with the universe of meanings, motives, beliefs, values, and attitudes, which corresponds to a more in-depth understanding of relationships, processes, and phenomena, contributing to the operationalization of variables. With the successful results of the research, demonstrating the community's potential for promoting fishing tourism and the conservation of natural and cultural heritage, it was possible to identify potential attractions, such as the existence of favorable conditions for fishing tourism due to the diversity of fish in the area. The community also participates in the Pé-de-Pincha Project. The region also boasts a diversity of birds and the community's traditional knowledge, which constitute an important source of cultural richness. From this identification, it was possible to describe the attractions and analyze and discuss the community's potential. The existence of tourism potential was confirmed; however, for the activity to be developed, community organization is necessary, especially regarding its structure and capacity building for providing tourism services.